DIRECTIVE UTTERANCES OF VERTICAL RELATIONSHIPS IN THE ANIME 'KAZE TACHINU' - Saputra, Ilham Winno; Bayu Aryanto (UIN Raden Mas Said Surakarta, 2024)
This study aimed at describing the directive utterances as well as the grammatical markers of the utterances in the conversations with vertical relations in the anime entitled Kaze Tachinu. This study used Searle's (1979) theory of directive speech acts and employed a descriptive-qualitative method. It also utilized sociopragmatic approach as an additional perspective in the analysis. The result shows that various forms of directive utterances are spoken by characters who have higher social status towards the others from the lower ones. In total, there are 48 directive utterances found for both direct and indirect categories. Meirei (command) dominates with 40 utterances and is followed by irai (request) kinshi (prohibition), kanyuu (invitation) and adobaisu(advice), each of which has two utterances.